2020
DOI: 10.1016/j.joca.2020.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Subregional statistical shape modelling identifies lesser trochanter size as a possible risk factor for radiographic hip osteoarthritis, a cross-sectional analysis from the Osteoporotic Fractures in Men Study

Abstract: Objective: Statistical shape modelling (SSM) of hip dual-energy X-ray absorptiometry (DXA) scans has identified relationships between hip shape and radiographic hip OA (rHOA). We aimed to further elucidate shape characteristics related to rHOA by focusing on subregions identified from whole-hip shape models. Method: SSM was applied to hip DXAs obtained in the Osteoporotic Fractures in Men Study. Whole-hip shape modes (HSMs) associated with rHOA were combined to form a composite at-risk-shape. Subsequently, sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 49 publications
1
13
2
Order By: Relevance
“…The associations between hip OA and both cam morphology and acetabular dysplasia have already been proven in other studies that used traditional measurements, such as the alpha angle and the CEA 7,8,10,28e35 . Two cross-sectional studies that used SSM also found associations between cam morphology and the presence of hip OA 36,37 . These studies were not included in our systematic review due to their cross-sectional design.…”
Section: Discussionmentioning
confidence: 97%
“…The associations between hip OA and both cam morphology and acetabular dysplasia have already been proven in other studies that used traditional measurements, such as the alpha angle and the CEA 7,8,10,28e35 . Two cross-sectional studies that used SSM also found associations between cam morphology and the presence of hip OA 36,37 . These studies were not included in our systematic review due to their cross-sectional design.…”
Section: Discussionmentioning
confidence: 97%
“…(6) SSM has identified relationships between HOA and a range of shape changes besides cam and pincer-type morphology, including femoral head size, femoral neck (FN) width, and lesser and greater trochanter size. (4,7) A possible explanation for the heterogeneous findings from different studies is the varying definitions used for HOA, including radiographic HOA (rHOA), symptomatic rHOA, and end-stage disease as reflected by THR.…”
Section: Introductionmentioning
confidence: 99%
“…The same genetic variants associated with hip shape and endochondral bone formation in adults appear to be important in adolescence [17]. Further work using SSM show that lesser trochanter size and cam-type FAI are related to radiographic OA [18].…”
Section: Hip Imaging Studiesmentioning
confidence: 85%